Implikasi Prinsip Sadd Adz-Żarā'i' dalam Menentukan Batasan Ghabn Fāḥisy pada Margin Keuntungan Murābaḥah - Sarwini; Zainol Huda (Al-Musthofa: Journal of Sharia Economics, 2025)
The determination of profit margins in murābaḥah contracts within Islamic financial institutions often raises ethical concerns due to its similarity to conventional interest, potentially conflicting with the maqāṣid al-sharī‘ah principle of justice. This study applies the uṣūl al-fiqh principle of sadd adz-żarā’i‘ (blocking the means to harm) to establish fair criteria for ghabn fāḥisy (excessive gain) in murābaḥah pricing. Using a qualitative library research method, it examines classical Mālikī and Ḥanbalī sources supporting sadd adz-żarā’i‘. Findings reveal that exploitative margins act as a strong żarī‘ah leading to ribā, making the application of sadd adz-żarā’i‘ obligatory. Hence, the threshold for ghabn fāḥisy should rely on equitable ‘urf tijārī (market custom) and real operational costs, ensuring murābaḥah remains just and consistent with ḥifẓ al-māl (protection of wealth).